Individual Responses for Muscle Activation, Repetitions, and Volume during Three Sets to Failure of High- (80% 1RM) versus Low-Load (30% 1RM) Forearm Flexion Resistance Exercise - Nathaniel D. M. Jenkins; Terry J. Housh; Samuel L. Buckner; Haley C. Bergstrom; Kristen C. Cochrane; Cory M. Smith; Ethan C. Hill; Richard J. Schmidt; Joel T. Cramer (MDPI AG, 2015)
This study compared electromyographic (EMG) amplitude, the number of repetitions completed, and exercise volume during three sets to failure of high- (80% 1RM) versus low-load (30% 1RM) forearm flexion resistance exercise on a subject-by-subject basis. Fifteen men were familiarized, completed forearm flexion 1RM testing. Forty-eight to 72 h later, the subjects completed three sets to failure of dumbbell forearm flexion resistance exercise with 80% (n = 8) or 30% (n = 7) 1RM. EMG amplitude was calculated for every repetition, and the number of repetitions performed and exercise volume were recorded. During sets 1, 2, and 3, one of eight subjects in the 80% 1RM group demonstrated a significant linear relationship for EMG amplitude versus repetition. For the 30% 1RM group, seven, five, and four of seven subjects demonstrated significant linear relationships during sets 1, 2, and 3, respectively. The mean EMG amplitude responses show that the fatigue-induced increases in EMG amplitude for the 30% 1RM group and no change in EMG amplitude for the 80% 1RM group resulted in similar levels of muscle activation in both groups. The numbers of repetitions completed were comparatively greater, while exercise volumes were similar in the 30% versus 80% 1RM group. Our results, in conjunction with those of previous studies in the leg extensors, suggest that there may be muscle specific differences in the responses to high- versus low-load exercise.